Use of a digital badge program on blended course students of an Institute of Superior Education - Gonzales López, Eduardo Fabio (2020)
This research aimed to promote the participation of a group of students of the blended course Organizational Behavior (Institute of Superior Education IDAT, Lima-Peru), from the implementation of a digital badge program in the institution’s LMS. The results showed that there was a participation percentage of 94,6%, which was higher by 61.2% compared to another course of the same group of students, and higher by 24.51% compared to the remain courses of the same period. In addition, a survey was applied to the students about their experience in this program. Further exploration of the impact of digital badge programs is required, using an experimental methodology.